Analisis Kinerja Motor DC 12 Volt Pengendali PID Menggunakan Pemodelan Blackbox dan Metode Tuning Ziegler-Nichols - Jordan Zefanya Purba; Indri Purwita Sary; Dian Budhi Santoso; Galih Setyaji; Rafli Gymnastiar (Jurnal Elektronika dan Otomasi Industri, 2026)
The speed control of a 12 Volt DC motor without feedback has limitations in maintaining stability and accuracy. This study aims to analyze the performance of the Proportional-Integral-Derivative (PID) control system on a 12 Volt DC motor using the blackbox modeling approach and the Ziegler–Nichols method. The system model was obtained based on the relationship between the input in the form of Pulse Width Modulation (PWM) and the motor speed output measured using a rotary encoder, then tuning the PID parameters through the Ziegler–Nichols method and refinement using trial and error based on Simulink simulation. The results showed that the system without PID had an overshoot of about 51% with a settling time of 0.6 seconds. After the implementation of PID, a significant improvement in system performance was observed with a reduction in overshoot of up to 2.9% and an acceleration of settling time to 0.25 seconds, resulting in a faster and more stable system response in reaching the setpoint.